2017
DOI: 10.1177/1076217517707236
|View full text |Cite
|
Sign up to set email alerts
|

Using Engineering Design Challenges to Engage Elementary Students With Gifts and Talents Across Multiple Content Areas

Abstract: With the release of the Next Generation Science Standards and the adoption of the standards by many states, teachers are encouraged to use the engineering design process (EDP) as an instructional approach to teaching science. However, teachers have limited time to teach science and will often neglect science in favor of mathematics and literacy instruction. To make this feasible for elementary classrooms, teachers should be encouraged to implement integrated units of study utilizing EDP to cohesively bind cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Technology and engineering education, career and technology education, and displine predecessors are ideally positioned for intersections of natural differentiation, relevancy, and creativity to benefit gifted students (Brenneman, Justice, & Curtis, 1980;Colson, Milburn, & Borman, 1983;Dailey, 2017;Dailey, Cotabish, & Jackson, 2018;Gentry, Hu, Peters, & Rizza, 2008;Mentzer, Reed, Alnouri, & Barbarji, 2018). According to Mann et al (2011):For students who have been identified as gifted but spend the majority of their day in regular education classrooms, engineering design activities present opportunities for varying levels of sophistication, breath, and depth of understanding, thus providing them with appropriately challenging tasks" (p. 651).…”
Section: The Federal Definition Of Giftedness Ismentioning
confidence: 99%
“…Technology and engineering education, career and technology education, and displine predecessors are ideally positioned for intersections of natural differentiation, relevancy, and creativity to benefit gifted students (Brenneman, Justice, & Curtis, 1980;Colson, Milburn, & Borman, 1983;Dailey, 2017;Dailey, Cotabish, & Jackson, 2018;Gentry, Hu, Peters, & Rizza, 2008;Mentzer, Reed, Alnouri, & Barbarji, 2018). According to Mann et al (2011):For students who have been identified as gifted but spend the majority of their day in regular education classrooms, engineering design activities present opportunities for varying levels of sophistication, breath, and depth of understanding, thus providing them with appropriately challenging tasks" (p. 651).…”
Section: The Federal Definition Of Giftedness Ismentioning
confidence: 99%
“…The rapid changes in the new world have brought the need for a quality STEM (Science, Technology, Engineering and Mathematics) education model content that will prepare students for future conditions in the education of gifted students, which has a significant impact on the development of societies (Dailey, 2017;Jolly, 2009) since gifted students need differentiated and enriched learning environment contents (Lee, Baek, & Lee, 2013). At the same time, gifted students have above-average science knowledge, creativity (Han and Shim, 2019), and high interest, talent (Lee, Matthews, Boo & Kim, 2020), and motivation (Jang, Chung, Choi, & Kim, 2013) to keep their interest in these areas alive, and it is important to provide opportunities.…”
Section: Introductionmentioning
confidence: 99%